1989
DOI: 10.1002/ssu.2980050507
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic neck dissection in squamous cell carcinoma of oral tongue: A prospective randomized study

Abstract: This paper presents the first report of an ongoing prospective randomised clinical trial in early T1T2N0 carcinoma of the oral tongue. The problems of regular follow-up in an indigent population from the vast rural expanse of India has been successfully overcome in this trial by close personal follow-up. The trial addresses itself specifically to prophylactic vs. therapeutic surgical management of the neck in T1T2N0 patients with cancer of the oral tongue. Overall disease, free survival (median follow-up 22 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 8 publications
(8 reference statements)
0
56
0
Order By: Relevance
“…This is in agreement with other reviews of SCCOT that demonstrate an incidence of occult lymph node disease of 20 -40%. [27][28][29][30][31][32][33] Although the presence of occult lymph node disease leads to stage migration, the presence of a single occult-positive lymph node did not have significant adverse effects on disease-specific survival in our study. In a review of 967 neck dissections, Byers 34 reported similar results when pathologic N1 disease was confined to the lymph node capsule.…”
Section: Discussionmentioning
confidence: 93%
“…This is in agreement with other reviews of SCCOT that demonstrate an incidence of occult lymph node disease of 20 -40%. [27][28][29][30][31][32][33] Although the presence of occult lymph node disease leads to stage migration, the presence of a single occult-positive lymph node did not have significant adverse effects on disease-specific survival in our study. In a review of 967 neck dissections, Byers 34 reported similar results when pathologic N1 disease was confined to the lymph node capsule.…”
Section: Discussionmentioning
confidence: 93%
“…They found that there was no survival difference between the two groups. They however found that a tumor depth of >4 mm was associated with higher rates of involved nodes and suggested that these set of patients may benefit from END [2]. A more recent RCT from Hong Kong compared END (supra-omohyoid neck dissection) versus observation for T1 and T2 lesions of the oral tongue.…”
Section: Discussionmentioning
confidence: 99%
“…To date four randomized control trials (RCT) have been conducted to address this issue. Two of these included only cancer of the tongue [2,3] and the other two [4,5] have included other early cancers of the oral cavity. However, the results of these trials have not provided a satisfactory answer to the controversy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of nodal metastasis is higher in tongue cancer patients than oral cavity cancer patients whose rate is 30% on their initial evaluation (8,9). Several studies have shown a high rate of occult nodal metastasis (20-40%) in tongue SCC patients with no evidence of regional spread on clinical or radiographic evaluation (8,(10)(11)(12)(13)(14)(15). There is a tendency that tongue cancer increases in young females in recent 2-3 decades (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%